Branding and media promotion strategies to enhance public interest in public high schools - Hasri Hidayat; Suparta Rasyid; Bahrun; Murniati AR (Indonesian Journal of Educational Development (IJED), 2026)
Branding and Media Promotion Strategies to Enhance Public Interest in Public High Schools. Rapid technological advancements and significant population growth are reshaping communication patterns, preferences, and societal behavior. This presents challenges for schools in effectively conducting outreach and promotion amidst increasingly fierce competition among educational institutions. This study aims to analyze Branding and Media Promotion Strategies to Enhance Public Interest. The research method used was a descriptive qualitative approach, with data collection techniques including passive participant observation, semi-structured interviews, and documentation. Research shows that branding strategies are implemented through the development of a structured promotional program timeline, ensuring each activity is documented and serves as an ongoing promotional tool. The curriculum governance strategy developed is not only oriented towards achieving national competency standards but is also tailored to local needs and student potential. This way, the curriculum becomes flexible and relevant, improving the quality of education and encouraging the achievement of more optimal learning objectives. These findings recommend that schools continue to optimize the use of technology media, strengthen collaboration, and adapt the curriculum to local needs as a sustainable branding strategy.